The law and penology of prison discipline - Quinn, Peter Michael (1989)
The study is of the disciplinary systems within the prisons of England and Wales. It concerns the response of the courts to prison matters brought before them and examines the effects upon prison life of an increasing demand for adherence to the rules of natural justice. Statutory authorities for the imposition of punishment within prison are reviewed as is the complex interweaving of statute, statutory instrument and internal regulations. There is a comprehensive examination of those parliamentary debates, conferences, committees of inquiry, reports and judgments that have influenced change. Particular reference is made to the question of legal or other assistance for an accused prisoner who faces a disciplinary hearing within the prison. The paper contains an account of the subsystems of discipline said to operate within penal establishments whereby the pressures of institutional life may conspire to prevent a prisoner receiving that to which he or she knows he or she is entitled. The paper draws upon the developing case law, the literature in the field and on private sources. The last of these includes the voice of prisoners themselves who are able to say how, if at all, a growing awareness by staff of the requirements of natural justice has affected the regime under which they live